提升一般與閱讀困難中學生的學科學習： 證據本位教學在普通課室之實踐 Improving Content Area Acquisition of Middle School Students With and Without Reading Difficulties: Evidencebased Instruction Implemented in General Education Classrooms - 王宣惠 Hsuan-Hui Wang; 洪儷瑜 Li-Yu Hung (National Changhua University of Education, 2023)
本研究主要目的在探討普通班學科閱讀教學對中學生學習表現的成效。本研究採準實驗設計，首先於台北地區招募國中社會領域教師參與者2人，實驗組學生即為教師參與者授課班級學生，共182人，對照組學生來自另一所學校，共119人，學生參與者皆為七、八年級學生，合計301人，實驗與對照組在閱讀相關能力基準線一致。實驗組教學為普通班第一層級社會領域學科閱讀教學，以海洋國家為議題，共6節課，於彈性課程實施。對照組學生則未接觸任何閱讀教學，也未接觸實驗教學之文本、材料。實驗教學之教材與教學資源皆由研究者設計提供，並透過教師專業發展培訓提供支持。為確保教師依據研究設計執行教學，本研究以教學觀察進行處遇精準度評量，包括教學忠誠度與教學傳遞品質。研究者首先以全體樣本檢驗實驗教學對整體學生的成效，再進一步於實驗、對照組區分出38與31位閱讀困難者，以進一步檢驗實驗教學對閱讀困難者之成效。研究發現實驗教學對中學生學科學習的近遷移有效，包括學科詞彙、知識與閱讀理解；此外，實驗教學亦有助於維持閱讀困難中學生的學科閱讀理解，顯示證據本位學科閱讀教學可於第一層級落實，並適用於所有學生。本研究基於上述研究結果，對中學階段學科教學實務提出建議。 This study examined the effects of a content area reading instruction (treatment) implemented by middle school social studies teachers. Two teacher participants were recruited from one public school in Taipei. Overall, 182 students from teacher participants' classes were recruited for treatment condition, and another 119 student participants were recruited for comparison from another public school. There were a total of 301 participants, all of which were seventh- and eighth-graders. Using a quasi-experimental design, baseline equivalence between treatment and comparison groups was established on the related reading measures. The treatment instruction was a Tier-1, six-session content area reading instruction focusing on ocean topics in social studies. All the treatment lessons, including detailed instructional scripts, texts, and teaching materials, were developed and provided to the teachers by the researcher. The comparison group was not exposed to any reading instructions, nor to the texts and materials of the treatment instruction. A treatment fidelity check including adherence and quality of delivery was conducted during the entire teaching by observations to ensure the treatment fidelity. The overall treatment effect on students was examined on the entire sample. Next, 38 and 31 students with reading difficulties were identified according to the general reading comprehension measure in both groups. The treatment effects on students with reading difficulties were further examined using this subsample. Results showed that students who received the treatment outperformed those in the comparison group on proximal measures, including academic vocabulary, content area knowledge, and content area reading comprehension. The content-area reading comprehension performance of students with reading difficulties remained consistent with treatment but significantly decreased in comparison. In addition, the results indicate that the treatment was facilitative for students both with and without reading difficulties in general classrooms, implying the effectiveness as well as the importance of the evidence-based content area reading instruction implemented in the Tier-1 setting. Further conclusions and suggestions concerning content area instructional practices were specified based on the findings of the study.